Bronze Stamps from Antioch-on-the-Orontes and Rest of Turkey: Antiochiae haereditati latinae, terrae motu destructae anno MMXXIII - Laflı, Ergün (Biblische Zeitschrift, 2025)
In this brief article we present a collection of eleven bronze bread stamps of the Early Byzantine period which are preserved in the Archaeological Museum of Hatay, i.e., ancient Antioch-on-the-Orontes in south-eastern Turkey that played a fundamental role in the shaping and developing of political life and cultures in the Greek, Roman and Byzantine East for more than a millennium. Eleven items are catalogued here in detail and identified as Late Antique-Early Byzantine bread stamps with, for the most part, Christian symbolism or connotations.